Identifying Putative Subsurface Microbial Drivers of Methane Flux on Earth and Mars - Sapers,Haley; Orphan,Victoria; Moores,John; Whyte,Lyle; Côté,Mathieu; Fecteau,Daniel; Grandmont,Frédéric; Innanen,Alex; Rusley,Calvin; Roux,Michel (ARPHA Conference Abstracts, 2023)
On Earth microorganisms are critical drivers of the methane cycle, both producing and consuming methane (Boetius et al. 2000, Knittel and Boetius 2009, Orphan et al. 2001). Molecular and isotopic-based investigations of archaeal-bacterial consortia catalyzing the anaerobic oxidation of methane (AOM) in marine methane seeps identified the pivotal role of these microorganisms in mitigating the release of methane into the atmosphere (Knittel and Boetius 2009, Orphan et al. 2001). In the marine environment, AOM is predominantly carried out by closely associated consortia of methanotrophic archaea (ANME) and sulfate reducing bacteria (SRB) coupling methane oxidation to sulfate reduction in the absence of oxygen.Wolf Spring (WS), Axel Heiberg Island, Nunavut is a hypersaline cold spring methane seep and the only known terrestrial permafrost hosted methane seep known to host ANME-1 archaea associated with AOM (Niederberger et al. 2010, Magnuson et al. 2022). Wolf Spring is an unparalleled analogue for putative subsurface brines and sites of methane release on Mars. Enigmatic observations of methane in the near-surface Martian atmosphere remain a tantalizing potential biosignature.The combination of field site characterization, microbial microcosm experiments, and in situ methane monitoring represents a coordinated interdisciplinary effort to identify methane driven microbial metabolisms not only critical to understanding methane flux in the Arctic, but also as possible drivers to the methane cycle on Mars. Detailed microbial characterization of these springs has identified a chemotrophic community dominated by sulfur cycling (Altshuler et al. 2022, Niederberger et al. 2010). To date, microbial and geochemical characterization has been carried out on sediment samples to a few centimeters depth. This study expands on these initial studies, with the successful collection and analysis of deeper sediment cores at WS focusing on AOM activity to better understand the microorganisms involved and the methane cycling capacity at ...